2020
DOI: 10.1002/msc.1481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water‐ and land‐based exercises on quality of life and physical aspects in women with fibromyalgia: A randomized clinical trial

Abstract: Introduction: Fibromyalgia (FM) is consistently associated with fatigue, sleep disturbances, morning stiffness, and anxiety and depression, affecting physical capacities and skills and thereby reducing quality of life. The aim of this study was to compare the effects of water-based and land-based therapies as an adjuvant treatment for women with FM in relation to quality of life and physical aspects. Methods: FM women were randomized into a water-based exercise group (WG) and land-based exercise group (LG). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…40,41 Our positive results for reducing the tender point counts in both groups was possible in less time as compared with other therapies. 41 One study demonstrates that fibromyalgia patients might have different fiber recruitment or a possible atrophy of type II fibers, suggesting that they are not able to reach muscle relaxation. 43 The current study justifies this result because we were not successful in modifying the EMG values at rest in either treatment used in our protocol.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…40,41 Our positive results for reducing the tender point counts in both groups was possible in less time as compared with other therapies. 41 One study demonstrates that fibromyalgia patients might have different fiber recruitment or a possible atrophy of type II fibers, suggesting that they are not able to reach muscle relaxation. 43 The current study justifies this result because we were not successful in modifying the EMG values at rest in either treatment used in our protocol.…”
Section: Discussionmentioning
confidence: 75%
“…Other justifications for our findings may be that exercise with exergaming might have promoted changes in brain dynamics such as increased power in the beta-3 frequency band that could be related to increased cerebral blood flow as described in another study. 18 The body of literature describes strengthening exercises, aerobic exercises, 40 water exercises, 41 and balneotherapy 42 reducing pain and improving tender point counts in adults with fibromyalgia. 40,41 Our positive results for reducing the tender point counts in both groups was possible in less time as compared with other therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the PRISMA flow diagram along with reasons for exclusion, with common reasons being no description of exercise mechanisms, non-randomized trials, pain outcomes not reported, and mean differences not being significant. The type of exercise interventions investigated in the RCTs are as follows: aquatic exercise (17 trials), [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] aerobic exercise (12 trials), 14,25,[28][29][30][31][32][33][34][35][36][37][38][39] resistance exercise (13 trials), 15,21,31,35,[40][41][42][43][44][45][46][47][48] flexibility exercise (7 trials), 28,32,40,…”
Section: Resultsmentioning
confidence: 99%
“…buoyancy, thermal effects, stimulation of tactile, mechanoreceptors, and relaxation) were more frequently identified (n = 12), 11,13,15,16,[18][19][20][21][22][23][24][25] followed by improvements in sleep (n = 6), 30,32,38,40,52,59 muscle oxygenation (n = 7), [12][13][14]30,31,40,58 and relaxation (n = 7). 11,14,15,20,23,52,54 Example of text verbatim. The pool-based environment, with its characteristics of buoyancy (which reduces the effects of gravity), the resistance of water (which reduces the impact on joints, muscles, and tendons), and the relaxing effect water has on muscles, prevent possible post-exercise pain and foster the benefits produced by the training session.…”
Section: Physical Categorymentioning
confidence: 99%